A capacitive flexible touch screen based on boron nitride and its preparation method
By using large-domain hexagonal boron nitride layer as a key material in capacitive flexible touch screen, the problem of poor electrical insulation and stability between indium tin oxide and OCA layer is solved, and high transparency, flexibility and electrical conductivity are achieved The touch electrode assembly improves the performance and reliability of the touch screen.
Patent Information
- Application Number
- CN202410995992.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-07-24
AI Technical Summary
There are problems of poor electrical insulation and stability between the existing indium tin oxide and optical transparent gel OCA layer, which affects the sensitivity and reliability of the touch screen.
The large-domain hexagonal boron nitride layer is used as the key material for transparent insulated boron nitride-based touch electrode module, and is prepared in an ultra-high vacuum environment by magnetron sputtering method to optimize the volume percentage of H2/Ar/N2 mixed gas. To improve the quality of the crystal domain.
Improves the transparency, flexibility and conductivity of the touch electrode assembly, enhances electrical insulation performance and chemical stability, and improves the overall performance and reliability of the touch screen.
Smart Images

Figure CN118939142B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible touch screens, and in particular to a boron nitride-based capacitive flexible touch screen and a preparation method thereof. Background Art
[0002] With the rapid development of information technology, the amount of information processed is increasing day by day, and it is urgent to improve the efficiency of human-computer interaction and design convenient input methods. The birth of touch screens has brought great changes to the field of electronics. The host can be operated by touching the screen with fingers, making human-computer interaction simpler and faster. At the same time, this device integrates input and output, promoting the development of electronic devices towards miniaturization and portability.
[0003] Capacitive flexible touch screen is a flexible screen that uses the principle of capacitive sensing to achieve touch screen function. It uses thin film materials and multi-layer structure, is flexible and bendable, and can adapt to devices of various shapes and sizes. Capacitive flexible touch screen has the advantages of high sensitivity, high precision and low power consumption, and can accurately identify the user's touch operation, providing a smooth and natural human-computer interaction experience. At the same time, due to its flexibility and bendability, capacitive flexible touch screen has broad application prospects in portable devices, wearable devices and other fields.
[0004] Typically, a capacitive touch screen is usually composed of modules such as a cover plate, a polarizer, a touch electrode, a display panel, and an underlying substrate. The touch electrode is also made of indium tin oxide electrode material, and the touch electrode and the display panel are usually bonded together with an optically transparent adhesive (OCA). Therefore, the optically transparent adhesive OCA needs to meet the following conditions: 1. High transparency: OCA needs to have high transparency to ensure the clarity and visual effect between the touch electrode and the display panel; 2. Electrical insulation: Since the touch electrode needs to transmit electrical signals, OCA needs to have electrical insulation to ensure the stability and safety of the signal; 3. Chemical stability and temperature resistance: The optically transparent adhesive OCA needs to have good temperature resistance and be able to maintain its chemical stability at various ambient temperatures; 4. Flexibility: The optically transparent adhesive OCA also needs to have a certain flexibility to adapt to the deformation and stress between the touch electrode and the display panel, and maintain the integrity and adhesion of the adhesive layer.
[0005] However, the current OCA and indium tin oxide electrode materials have the following problems: 1. Electrical insulation problem: Optically transparent adhesive OCA needs to have good electrical insulation to prevent current from leaking or interfering in the adhesive layer, affecting the sensitivity and stability of the touch screen. However, OCA is a polymer material, and there are usually many defects at the interface between OCA and indium tin oxide, such as vacancies, impurities, and bubbles, which will increase the scattering of electrons during the conduction process. Therefore, there are conductivity or electrical connection problems between indium tin oxide and OCA, which may cause interference or false touch of touch signals; 2. Optically transparent adhesive OCA and indium tin oxide need to have good temperature resistance and chemical stability, and be able to maintain their performance and adhesion in high temperature environments. If the temperature exceeds the temperature resistance range of optically transparent adhesive OCA and indium tin oxide, it may cause thermal decomposition, failure, or reduced adhesion of the adhesive layer, thereby affecting the sensitivity and reliability of the touch layer. Therefore, it is necessary to further solve the problems of poor electrical insulation and stability between indium tin oxide and OCA to meet a wider range of application needs.
[0006] Hexagonal boron nitride is a material with unique properties. It has excellent transparency, electrical insulation, flexibility and chemical stability. First, hexagonal boron nitride has high optical transparency, with a transmittance of 85-95%, making it an ideal transparent material. Second, hexagonal boron nitride has excellent electrical insulation properties, with an insulation resistance of up to 10 12Ω·cm, making it an ideal insulating material for electronic devices. The paper "Boron nitride substrates for high-quality graphene electronics. Nature Nanotechnology 5.10 (2010): 722-726." reported that the field effect transistor prepared with hexagonal boron nitride as the insulating substrate has a carrier mobility three times higher than that of the traditional SiO2 substrate, showing the excellent electrical insulation performance of hexagonal boron nitride. In addition, hexagonal boron nitride is also very flexible and can be bent and folded. The paper "Flexible and Transparent MoS2 Field-Effect Transistors on HexagonalBoron Nitride-Graphene Heterostructures. ACS Nano 7.9 (2013): 7931–7936." reported that a flexible and highly transparent field effect transistor was prepared with hexagonal boron nitride as the flexible substrate, proving that it has broad application prospects in flexible electronics and wearable devices. Finally, hexagonal boron nitride also has excellent chemical stability and can remain stable in harsh environments such as high temperature and strong acid and alkali, giving it broad application prospects in the chemical industry and high-temperature applications. However, there is currently no literature reporting that hexagonal boron nitride can be used in the field of flexible capacitive touch screens. Summary of the invention
[0007] The purpose of the present invention is to provide a capacitive flexible touch screen based on boron nitride and a preparation method thereof. The capacitive flexible touch screen based on boron nitride has high transparency, good electrical insulation and strong chemical stability, high performance and reliability, and can solve the problems of poor electrical insulation and stability between the existing indium tin oxide and OCA layer.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A capacitive flexible touch screen based on boron nitride, the capacitive flexible touch screen comprising, from top to bottom, a multifunctional film layer, a flexible film cover, a polarizer, a transparent insulating boron nitride-based touch electrode module, a film encapsulation layer, a flexible support layer, a buffer layer and a flexible metal layer; the transparent insulating boron nitride-based touch electrode module comprises, from top to bottom, a first boron nitride layer, an upper indium tin oxide film, a second boron nitride layer, a fifth optically transparent adhesive (OCA) layer, a third boron nitride layer, a lower indium tin oxide film and a fourth boron nitride layer; the first boron nitride layer, the second boron nitride layer, the third boron nitride layer and the fourth boron nitride layer are all hexagonal boron nitride layers.
[0010] Furthermore, the hexagonal boron nitride layer is a large crystal domain hexagonal boron nitride layer, and the average crystal domain of the hexagonal boron nitride is 2 to 6 mm;
[0011] The thickness of the first boron nitride layer, the second boron nitride layer, the third boron nitride layer and the fourth boron nitride layer is 5-25 nm.
[0012] The present invention designs a large-domain hexagonal boron nitride layer with an average thickness of 5 to 25 nm and an average domain of 2 to 6 mm, with the aim of improving the transparency, flexibility and conductivity of the boron nitride-based touch electrode module. First, the average domain of hexagonal boron nitride is 2 to 6 mm, which means that boron nitride has high crystallinity and very few grain boundaries, and therefore has a more ordered lattice arrangement, which reduces the scattering of light and improves the transparency of the material. By reducing defects through high crystallinity, the scattering and absorption of light can be reduced, further improving transparency. At the same time, reducing defects can also reduce the scattering of electrons and improve the conductivity of the indium tin oxide conductive layer. Hexagonal boron nitride is an insulating substrate with excellent performance, which can reduce the electron scattering of indium tin oxide and improve its conductivity. The boron nitride layer with high crystallinity and few defects can more effectively reduce the electron scattering of indium tin oxide and improve the conductivity and response speed of the touch electrode assembly. In addition, materials with good crystallinity have better mechanical properties, can maintain the integrity of the structure when bent or twisted, and enhance the flexibility of the touch electrode assembly. In summary, by controlling the average thickness and grain size of the large-domain hexagonal boron nitride layer, high crystallinity and few defects can be achieved, thereby improving the transparency, flexibility and conductivity of the boron nitride-based touch electrode assembly and reducing energy consumption.
[0013] Furthermore, the method for preparing the transparent insulating boron nitride-based touch electrode module comprises the following steps:
[0014] S1: magnetron sputtering an indium tin oxide film on a copper foil, then patterning the indium tin oxide film, and then etching the copper foil with FeCl3 having a mass concentration of 5 to 15%, and using the prepared indium tin oxide film as an upper indium tin oxide film and a lower indium tin oxide film;
[0015] S2: Using a magnetron sputtering method, the upper indium tin oxide film and the lower indium tin oxide film are suspended in a magnetron sputtering chamber, and the first boron nitride layer and the second boron nitride layer are sputtered on the upper and lower surfaces of the upper indium tin oxide film, respectively, and the third boron nitride layer and the fourth boron nitride layer are sputtered on the upper and lower surfaces of the lower indium tin oxide film, respectively, and then the second boron nitride layer and the third boron nitride layer are bonded by a fifth optically transparent adhesive OCA layer, and finally a transparent insulating boron nitride-based touch electrode module is obtained.
[0016] Furthermore, the magnetron sputtering method includes: at a base pressure of 2×10 -10In Torr's ultra-high vacuum magnetron sputtering chamber, a high-purity H2 / Ar / N2 mixed gas is used as the reaction gas. The volume percentages of H2, Ar, and N2 in the H2 / Ar / N2 mixed gas are 6-10%, 45-47%, and 45-47%, respectively. High-purity boron palladium is used as the boron source, and the sputtering pressure is (1-3)×10 - 2 Torr, the sputtering power is 6 to 10 W, and the sputtering time is 15 to 45 min.
[0017] When preparing large-domain hexagonal boron nitride, the present invention adopts an ultra-high vacuum system and limits the volume percentage of H2 in the H2 / Ar / N2 mixed gas to 6-10%), the purpose of which is to improve the crystal domain of hexagonal boron nitride. First, the ultra-high vacuum system provides a highly pure preparation environment, avoiding pollution and interference from external impurities, which is conducive to the growth of high-quality large-domain hexagonal boron nitride films. Limiting the volume percentage of H2 in the H2 / Ar / N2 mixed gas to 6-10% is to optimize the composition and flow rate of the atmosphere gas to promote the growth of large-domain hexagonal boron nitride. An appropriate amount of H2 provides a reducing agent to promote the growth rate and crystal quality of the boron nitride film; an appropriate amount of Ar dilutes the atmosphere, reduces the gas pressure and flow rate, and is conducive to the growth and uniformity of the crystal; an appropriate amount of N2 adjusts the atmosphere composition and provides a suitable nitrogen source and atmosphere stability. However, it should be noted that during the growth of hexagonal boron nitride, the presence of H2 can etch the amorphous boron nitride layer to obtain a purer hexagonal boron nitride film.
[0018] Furthermore, the thickness of the upper indium tin oxide film and the lower indium tin oxide film is 50-125 μm, and the thickness of the fifth optically transparent adhesive OCA layer is 30-70 μm.
[0019] Furthermore, the flexible film cover is a highly transparent polyimide film; the thickness of the highly transparent polyimide film is 50 to 150 μm; and the full spectrum transmittance of the highly transparent polyimide film is greater than 90%.
[0020] Furthermore, the preparation method of the highly transparent polyimide film is as follows: a polyamic acid solution uniformly mixed with diisopropyl phthalate, 4,4'-difluorophthalic anhydride and dimethyl sulfoxide in a molar ratio of 1:1:4 is coated on a glass substrate by an extrusion coating method, and then the coated substrate is placed in an oven and heat-treated at 250 to 400°C to promote the polymerization reaction of the polyamic acid solution to form a polyimide film. After the heat treatment is completed, the temperature is cooled to room temperature at a cooling rate of 0.2 to 2°C / min, and the polyimide is demolded from the substrate to obtain a highly transparent polyimide film after treatment.
[0021] Furthermore, the multifunctional film layer is an anti-glare film or an anti-scattering film, and the thickness of the multifunctional film layer is 10 to 25 μm;
[0022] The polarizer is a polycarbonate film with a thickness of 40 to 80 μm;
[0023] Furthermore, the film encapsulation layer is a polyethylene film or a polyester film with a thickness of 40 to 90 μm;
[0024] The flexible support layer is a polyimide film or a polyethylene terephthalate film with a thickness of 20 to 50 μm;
[0025] The buffer layer is a polyurethane foam layer or a polyacrylate foam layer, with a thickness of 100 to 200 μm and a porosity of 20 to 50%;
[0026] The flexible metal layer is a stainless steel layer or an aluminum foil layer, and has a thickness of 50 to 120 μm.
[0027] Furthermore, the multifunctional film layer and the flexible film cover are bonded by a first optically transparent adhesive OCA layer; the flexible film cover and the polarizer are bonded by a second optically transparent adhesive OCA layer; the polarizer and the touch electrode assembly are bonded by a third optically transparent adhesive OCA layer; the film encapsulation layer and the flexible support layer are bonded by a fourth optically transparent adhesive OCA layer;
[0028] The thickness of the first optically transparent adhesive OCA layer, the second optically transparent adhesive OCA layer, the third optically transparent adhesive OCA layer and the fourth optically transparent adhesive OCA layer are all 20-100 μm.
[0029] As a general inventive concept, the present invention also provides a method for preparing a capacitive flexible touch screen based on boron nitride, comprising the following steps:
[0030] First, a large-area flexible metal layer is prepared, and then a buffer layer and a flexible support layer are prepared on it in sequence, and then the lower surface of the transparent insulating boron nitride-based touch electrode module is encapsulated with a thin film encapsulation layer, and the thin film encapsulation layer is bonded to the flexible support layer through a fourth optically transparent adhesive OCA layer; then, the polarizer is bonded to the upper surface of the transparent insulating boron nitride-based touch electrode module through a third optically transparent adhesive OCA layer in sequence; then, the flexible film cover is bonded to the upper surface of the polarizer through a second optically transparent adhesive OCA layer; finally, the multifunctional film layer is bonded to the upper surface of the flexible film cover through a first optically transparent adhesive OCA layer to complete the preparation of the capacitive flexible touch screen.
[0031] The present invention has the following beneficial effects:
[0032] 1. The large crystal domain boron nitride layers arranged in the transparent insulating boron nitride-based touch electrode module of the present invention all have excellent optical transparency. The bonding method in the crystal structure of the boron nitride layer allows light to pass through effectively without being absorbed or scattered. Therefore, the boron nitride layer is arranged on the upper and lower sides of the indium tin oxide film, which can also enable the touch screen to maintain high transparency and make the displayed content clearly visible. The large band gap width in the electronic structure based on boron nitride makes it difficult for electrons to pass through, thereby effectively isolating the capacitive electrodes on the touch screen. The electrical insulation performance can prevent current leakage or interference and improve the accuracy and reliability of the touch signal. In addition, the boron nitride structure is stable and can withstand corrosion and oxidation by a variety of chemical substances. Boron nitride has strong chemical stability. Finally, the large crystal domain boron nitride base can improve the transparency, flexibility and conductivity of the touch electrode assembly. The high crystallinity of boron nitride reduces light scattering, improves transparency, and reduces the electron scattering of the indium tin oxide (ITO) conductive layer, thereby improving its conductivity. At the same time, good crystallinity also enhances the mechanical properties of the material, making the touch electrode assembly more flexible. This design not only optimizes performance, but also reduces energy consumption, so that the boron nitride-based touch screen of the present invention can operate stably for a long time under various environmental conditions and is not easily affected by external factors.
[0033] 2. In the present invention, the transparent insulating boron nitride-based touch electrode module includes, from top to bottom, a first boron nitride layer, an upper indium tin oxide film, a second boron nitride layer, a fifth optically transparent adhesive OCA layer, a third boron nitride layer, a lower indium tin oxide film, and a fourth boron nitride layer. This design achieves multiple beneficial effects. First, the first boron nitride layer has good optical transparency, which improves the transparency and display effect of the touch screen; the upper indium tin oxide film and the lower indium tin oxide film serve as conductive layers, providing high conductivity and enhancing the sensitivity and response speed of the touch screen; the excellent mechanical properties of the second boron nitride layer maintain the flexibility and durability of the touch screen; the fifth optically transparent adhesive OCA layer improves the optical quality and makes the displayed content more clearly visible; the third boron nitride layer, as an insulating layer, isolates the upper and lower indium tin oxide films, improving the accuracy and reliability of the touch signal; the fourth boron nitride layer has strong chemical stability, protecting the lower components from damage. At the same time, the hexagonal boron nitride layer in the present invention has excellent flatness, can provide a uniform contact area and a better current transmission effect, thereby further improving the sensitivity, response speed and display effect of the touch screen.
[0034] Furthermore, the boron nitride layer is arranged between indium tin oxide and OCA. Since hexagonal boron nitride has good flatness, flexibility and the characteristics of no hanging bonds, it can effectively reduce defects such as bubbles and vacancies on the interface of indium tin oxide and OCA. These defects will affect the electrical insulation, and the application of boron nitride can improve the electrical insulation performance and enhance the stability and reliability of the touch electrode assembly. In addition, boron nitride has high temperature stability and can maintain stable performance under high temperature environment. This feature further improves the temperature resistance and chemical stability of the boron nitride-based touch electrode assembly under high temperature conditions. Under high temperature environment, traditional materials may have problems such as expansion, deformation or degradation, and the use of boron nitride can avoid these problems and extend the service life of the touch electrode assembly. In summary, through the above-mentioned structural setting and the flatness optimization of the hexagonal boron nitride layer, the present invention can achieve the optimized design of the transparent insulating boron nitride-based touch electrode assembly, improve the transparency, sensitivity, durability and reliability, thereby improving the overall performance of the touch screen.
[0035] 3. When preparing a transparent insulating boron nitride-based touch electrode module, the present invention optimizes the volume percentage of the H2 / Ar / N2 mixed gas through an ultra-high vacuum system to prepare large-domain hexagonal boron nitride. The ultra-high vacuum ensures the purity of the preparation environment, avoids interference from impurities, and promotes the growth of high-quality large-domain thin films. In the mixed gas, an appropriate amount of H2 provides a reducing effect, Ar dilutes the atmosphere to promote crystal growth and uniformity, and N2 adjusts the atmosphere composition and provides a nitrogen source. In addition, H2 also helps to etch the amorphous boron nitride layer and improve the purity of the film.
[0036] 4. The highly transparent polyimide film prepared by the method of the present invention has high transparency and high flexibility. It cooperates with other components of the capacitive flexible touch screen of the present invention to achieve excellent touch screen performance. First, the highly transparent polyimide film can provide a clear and visible display effect, making the content displayed on the touch screen vivid and delicate. It has a high transmittance, can reduce the scattering and reflection of light, and make the display quality of the touch screen more outstanding. Secondly, the highly flexible polyimide film can adapt to various curved shapes and bending operations, and provide a comfortable touch experience. It has good bendability and resilience, and the touch screen can still work normally even when bent and deformed, without affecting the accuracy and sensitivity of the touch. In addition, the polyimide film has excellent durability, can resist wear, scratches and chemical corrosion, effectively protects the display layer and touch sensor of the touch screen, and prolongs the service life of the touch screen. Finally, the light and thin design of the polyimide film makes the touch screen more lightweight and comfortable, easy to carry and operate. In summary, the application of the highly transparent polyimide film prepared by the method of the present invention in the capacitive flexible touch screen has the advantages of high transparency and high flexibility, and can provide high-quality display effects and touch experience.
[0037] 5. In summary, the capacitive flexible touch screen based on boron nitride of the present invention has high transparency, good electrical insulation and strong chemical stability, which interacts with the working principle of the touch screen, making it suitable for various application fields and having high performance and reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a structural schematic diagram of the capacitive flexible touch screen of the present invention;
[0039] Figure 2 for Figure 1 A schematic diagram of the enlarged structure at A in the middle;
[0040] Figure 3 This is a photo of the local microstructure of the flexible touch screen prepared in Example 1 of the present invention;
[0041] Figure 4 TEM microstructure photos of the indium tin oxide layer and the hexagonal boron nitride layer prepared in Example 1 of the present invention;
[0042] Figure 5 This is a Raman spectrum of hexagonal boron nitride prepared in Example 1 of the present invention.
[0043] In the figure: 1. multifunctional film layer; 2. first optically transparent adhesive OCA layer; 3. flexible film cover; 4. second optically transparent adhesive OCA layer; 5. polarizer; 6. third optically transparent adhesive OCA layer; 7. transparent insulating boron nitride-based touch electrode module; 71. first boron nitride layer; 72. upper indium tin oxide film; 73. second boron nitride layer; 74. fifth optically transparent adhesive OCA layer; 75. third boron nitride layer; 76. lower indium tin oxide film; 77. fourth boron nitride layer; 8. film encapsulation layer; 9. fourth optically transparent adhesive OCA layer; 10. flexible support layer; 11. buffer layer; 12. flexible metal layer. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0045] Embodiment 1:
[0046] like Figure 1-2As shown, a capacitive flexible touch screen based on boron nitride includes, from top to bottom, a multifunctional film layer 1, a flexible film cover plate 3, a polarizer 5, a transparent insulating boron nitride-based touch electrode module 7, a film encapsulation layer 8, a flexible support layer 10, a buffer layer 11 and a flexible metal layer 12; the multifunctional film layer 1 and the flexible film cover plate 3 are bonded by a first optically transparent adhesive OCA layer 2; the flexible film cover plate 3 and the polarizer 5 are bonded by a second optically transparent adhesive OCA layer 4; the polarizer 5 and the touch electrode module 7 are bonded by a third optically transparent adhesive OCA layer 6; the film encapsulation layer 8 and the flexible support layer 10 are bonded by a fourth optically transparent adhesive OCA layer 9.
[0047] The transparent insulating boron nitride-based touch electrode module 7 includes, from top to bottom, a first boron nitride layer 71, an upper indium tin oxide film 72, a second boron nitride layer 73, a fifth optically transparent adhesive OCA layer 74, a third boron nitride layer 75, a lower indium tin oxide film 76 and a fourth boron nitride layer 77; the first boron nitride layer 71, the second boron nitride layer 73, the third boron nitride layer 75 and the fourth boron nitride layer 77 are all large-domain hexagonal boron nitride layers, and the average crystal domain of the hexagonal boron nitride is 2 mm.
[0048] The thickness of the first boron nitride layer 71 , the second boron nitride layer 73 , the third boron nitride layer 75 and the fourth boron nitride layer 77 are all 10 nm; the thickness of the upper indium tin oxide film 72 and the lower indium tin oxide film 76 are all 100 μm.
[0049] The thickness of the first optically transparent adhesive OCA layer 2 is 20 μm, the thickness of the second optically transparent adhesive OCA layer 4 , the third optically transparent adhesive OCA layer 6 and the fourth optically transparent adhesive OCA layer 9 are all 25 μm; the thickness of the fifth optically transparent adhesive OCA layer 74 is 50 μm.
[0050] The method for preparing the transparent insulating boron nitride-based touch electrode module 7 comprises the following steps:
[0051] S1: magnetron sputtering an indium tin oxide film on a copper foil, then patterning the indium tin oxide film, and then etching the copper foil with FeCl3 having a mass concentration of 5%, to obtain an upper indium tin oxide film 72 and a lower indium tin oxide film 76;
[0052] S2: Using magnetron sputtering, suspend the upper indium tin oxide film 72 and the lower indium tin oxide film 76 in the magnetron sputtering chamber, sputter the first boron nitride layer 71 and the second boron nitride layer 73 on the upper and lower surfaces of the upper indium tin oxide film 72, respectively, and sputter the third boron nitride layer 75 and the fourth boron nitride layer 77 on the upper and lower surfaces of the lower indium tin oxide film 76, respectively, and then bond the second boron nitride layer 73 and the third boron nitride layer 75 respectively through the fifth optically transparent adhesive OCA layer 74, and finally obtain a transparent insulating boron nitride-based touch electrode module 7.
[0053] The magnetron sputtering method includes: at a base pressure of 2×10 -10 In Torr's ultra-high vacuum magnetron sputtering chamber, a high-purity H2 / Ar / N2 mixed gas is used as the reaction gas. The volume percentages of H2, Ar, and N2 in the H2 / Ar / N2 mixed gas are 6%, 47%, and 47%, respectively. High-purity boron palladium is used as the boron source, and the sputtering pressure is 1×10 -2 Torr, the sputtering power is 6W, and the sputtering time is 15min.
[0054] In this embodiment, the flexible film cover plate 3 is a highly transparent polyimide film; the thickness of the highly transparent polyimide film is 50 μm; and the full spectrum transmittance of the highly transparent polyimide film is 93%.
[0055] The preparation method of a highly transparent polyimide film is as follows: a polyamic acid solution prepared by uniformly mixing diisopropyl phthalate, 4,4'-difluorophthalic anhydride and dimethyl sulfoxide in a molar ratio of 1:1:4 is coated on a glass substrate by an extrusion coating method; then, the coated substrate is placed in an oven and subjected to a heat treatment at 300°C to promote the polymerization reaction of the polyamic acid solution to form a polyimide film; after the heat treatment is completed, the temperature is cooled to room temperature at a cooling rate of 1°C / min, and the polyimide is demolded from the substrate to obtain a highly transparent polyimide film after treatment.
[0056] In this embodiment, the multifunctional film layer 1 is an anti-glare film, and the thickness of the multifunctional film layer 1 is 10 μm; the polarizer 5 is a polycarbonate film, and the thickness is 50 μm; the film encapsulation layer 8 is a polyethylene film, and the thickness is 40 μm; the flexible supporting layer 10 is a polyimide film, and the thickness is 50 μm; the buffer layer 11 is a polyurethane foam layer, and the thickness is 100 μm, and the porosity is 20%; the flexible metal layer 12 is a stainless steel layer, and the thickness is 50 μm.
[0057] The method for preparing the above-mentioned capacitive flexible touch screen based on boron nitride comprises the following steps:
[0058] First, prepare a large-area flexible metal layer 12, and then prepare a buffer layer 11 and a flexible support layer 10 thereon in sequence, then encapsulate the lower surface of the transparent insulating boron nitride-based touch electrode module 7 with a thin film encapsulation layer 8, and bond the thin film encapsulation layer 8 to the flexible support layer 10 through a fourth optically transparent adhesive OCA layer 9; then, sequentially bond the polarizer 5 to the upper surface of the transparent insulating boron nitride-based touch electrode module 7 through a third optically transparent adhesive OCA layer 6; then, bond the flexible film cover 3 to the upper surface of the polarizer 5 through a second optically transparent adhesive OCA layer 4; finally, bond the multifunctional film layer 1 to the upper surface of the flexible film cover 3 through a first optically transparent adhesive OCA layer 2, and the preparation of the capacitive flexible touch screen is completed.
[0059] Figure 3 This is a photo of the local microstructure of the flexible touch screen prepared in this embodiment. It can be clearly seen that the layers are well bonded;
[0060] Figure 4 This is a TEM microstructure photograph of the indium tin oxide layer and the hexagonal boron nitride layer prepared in this embodiment. It can be clearly seen that the hexagonal boron nitride is evenly covered on the surface of the indium tin oxide, and the interface bonding is good.
[0061] Figure 5 This is the Raman spectrum of the hexagonal boron nitride prepared in this example. From the Raman peak, it can be clearly seen that the prepared substance is hexagonal boron nitride.
[0062] Embodiment 2:
[0063] like Figure 1-2 As shown, a capacitive flexible touch screen based on boron nitride includes, from top to bottom, a multifunctional film layer 1, a flexible film cover plate 3, a polarizer 5, a transparent insulating boron nitride-based touch electrode module 7, a film encapsulation layer 8, a flexible support layer 10, a buffer layer 11 and a flexible metal layer 12; the multifunctional film layer 1 and the flexible film cover plate 3 are bonded by a first optically transparent adhesive OCA layer 2; the flexible film cover plate 3 and the polarizer 5 are bonded by a second optically transparent adhesive OCA layer 4; the polarizer 5 and the touch electrode module 7 are bonded by a third optically transparent adhesive OCA layer 6; the film encapsulation layer 8 and the flexible support layer 10 are bonded by a fourth optically transparent adhesive OCA layer 9.
[0064] The transparent insulating boron nitride-based touch electrode module 7 includes, from top to bottom, a first boron nitride layer 71, an upper indium tin oxide film 72, a second boron nitride layer 73, a fifth optically transparent adhesive OCA layer 74, a third boron nitride layer 75, a lower indium tin oxide film 76 and a fourth boron nitride layer 77; the first boron nitride layer 71, the second boron nitride layer 73, the third boron nitride layer 75 and the fourth boron nitride layer 77 are all large-domain hexagonal boron nitride layers, and the average crystal domain of the hexagonal boron nitride is 3 mm.
[0065] The thickness of the first boron nitride layer 71, the second boron nitride layer 73, the third boron nitride layer 75 and the fourth boron nitride layer 77 is 15 nm; the thickness of the upper indium tin oxide film 72 and the lower indium tin oxide film 76 is 65 μm.
[0066] The thickness of the first optically transparent adhesive OCA layer 2 is 25 μm, the thickness of the second optically transparent adhesive OCA layer 4 , the third optically transparent adhesive OCA layer 6 and the fourth optically transparent adhesive OCA layer 9 are all 50 μm; the thickness of the fifth optically transparent adhesive OCA layer 74 is 50 μm.
[0067] The method for preparing the transparent insulating boron nitride-based touch electrode module 7 comprises the following steps:
[0068] S1: magnetron sputtering an indium tin oxide film on a copper foil, then patterning the indium tin oxide film, and then etching the copper foil with FeCl3 having a mass concentration of 10%, to obtain an upper indium tin oxide film 72 and a lower indium tin oxide film 76;
[0069] S2: Using magnetron sputtering, suspend the upper indium tin oxide film 72 and the lower indium tin oxide film 76 in the magnetron sputtering chamber, sputter the first boron nitride layer 71 and the second boron nitride layer 73 on the upper and lower surfaces of the upper indium tin oxide film 72, respectively, and sputter the third boron nitride layer 75 and the fourth boron nitride layer 77 on the upper and lower surfaces of the lower indium tin oxide film 76, respectively, and then bond the second boron nitride layer 73 and the third boron nitride layer 75 respectively through the fifth optically transparent adhesive OCA layer 74, and finally obtain a transparent insulating boron nitride-based touch electrode module 7.
[0070] The magnetron sputtering method includes: at a base pressure of 2×10 -10 In Torr's ultra-high vacuum magnetron sputtering chamber, a high-purity H2 / Ar / N2 mixed gas is used as the reaction gas. The volume percentages of H2, Ar, and N2 in the H2 / Ar / N2 mixed gas are 8%, 46%, and 46%, respectively. High-purity boron palladium is used as the boron source, and the sputtering pressure is 2×10 -2 Torr, the sputtering power is 8W, and the sputtering time is 30min.
[0071] In this embodiment, the flexible film cover plate 3 is a highly transparent polyimide film; the thickness of the highly transparent polyimide film is 60 μm; and the full spectrum transmittance of the highly transparent polyimide film is 93%.
[0072] The preparation method of a highly transparent polyimide film is as follows: a polyamic acid solution prepared by uniformly mixing diisopropyl phthalate, 4,4'-difluorophthalic anhydride and dimethyl sulfoxide in a molar ratio of 1:1:4 is coated on a glass substrate by an extrusion coating method; then, the coated substrate is placed in an oven and subjected to a heat treatment at 350°C to promote the polymerization reaction of the polyamic acid solution to form a polyimide film; after the heat treatment is completed, the temperature is lowered to room temperature at a cooling rate of 0.2°C / min, and the polyimide is demolded from the substrate to obtain a highly transparent polyimide film after treatment.
[0073] In this embodiment, the multifunctional film layer 1 is an anti-scattering film, and the thickness of the multifunctional film layer 1 is 5 μm; the polarizer 5 is a polycarbonate film, and the thickness is 60 μm; the film encapsulation layer 8 is a polyester film, and the thickness is 50 μm; the flexible supporting layer 10 is a polyethylene terephthalate film, and the thickness is 30 μm; the buffer layer 11 is a polyacrylate foam layer, and the thickness is 150 μm, and the porosity is 30%; the flexible metal layer 12 is an aluminum foil layer, and the thickness is 60 μm.
[0074] The preparation method of the above-mentioned boron nitride-based capacitive flexible touch screen is the same as that of Example 1.
[0075] Embodiment 3:
[0076] like Figure 1-2 As shown, a capacitive flexible touch screen based on boron nitride includes, from top to bottom, a multifunctional film layer 1, a flexible film cover plate 3, a polarizer 5, a transparent insulating boron nitride-based touch electrode module 7, a film encapsulation layer 8, a flexible support layer 10, a buffer layer 11 and a flexible metal layer 12; the multifunctional film layer 1 and the flexible film cover plate 3 are bonded by a first optically transparent adhesive OCA layer 2; the flexible film cover plate 3 and the polarizer 5 are bonded by a second optically transparent adhesive OCA layer 4; the polarizer 5 and the touch electrode module 7 are bonded by a third optically transparent adhesive OCA layer 6; the film encapsulation layer 8 and the flexible support layer 10 are bonded by a fourth optically transparent adhesive OCA layer 9.
[0077] The transparent insulating boron nitride-based touch electrode module 7 includes, from top to bottom, a first boron nitride layer 71, an upper indium tin oxide film 72, a second boron nitride layer 73, a fifth optically transparent adhesive OCA layer 74, a third boron nitride layer 75, a lower indium tin oxide film 76 and a fourth boron nitride layer 77; the first boron nitride layer 71, the second boron nitride layer 73, the third boron nitride layer 75 and the fourth boron nitride layer 77 are all large-domain hexagonal boron nitride layers, and the average crystal domain of the hexagonal boron nitride is 6 mm.
[0078] The thickness of the first boron nitride layer 71, the second boron nitride layer 73, the third boron nitride layer 75 and the fourth boron nitride layer 77 are all 22 nm; the thickness of the upper indium tin oxide film 72 and the lower indium tin oxide film 76 are all 75 μm.
[0079] The thickness of the first optically transparent adhesive OCA layer 2 is 50 μm, the thickness of the second optically transparent adhesive OCA layer 4 , the third optically transparent adhesive OCA layer 6 and the fourth optically transparent adhesive OCA layer 9 are all 80 μm; the thickness of the fifth optically transparent adhesive OCA layer 74 is 50 μm.
[0080] The method for preparing the transparent insulating boron nitride-based touch electrode module 7 comprises the following steps:
[0081] S1: magnetron sputtering an indium tin oxide film on a copper foil, then patterning the indium tin oxide film, and then etching the copper foil with FeCl3 having a mass concentration of 15%, to obtain an upper indium tin oxide film 72 and a lower indium tin oxide film 76;
[0082] S2: Using magnetron sputtering, suspend the upper indium tin oxide film 72 and the lower indium tin oxide film 76 in the magnetron sputtering chamber, sputter the first boron nitride layer 71 and the second boron nitride layer 73 on the upper and lower surfaces of the upper indium tin oxide film 72, respectively, and sputter the third boron nitride layer 75 and the fourth boron nitride layer 77 on the upper and lower surfaces of the lower indium tin oxide film 76, respectively, and then bond the second boron nitride layer 73 and the third boron nitride layer 75 respectively through the fifth optically transparent adhesive OCA layer 74, and finally obtain a transparent insulating boron nitride-based touch electrode module 7.
[0083] The magnetron sputtering method includes the following steps: at a base pressure of 2×10 -10 In Torr's ultra-high vacuum magnetron sputtering chamber, a high-purity H2 / Ar / N2 mixed gas is used as the reaction gas. The volume percentages of H2, Ar, and N2 in the H2 / Ar / N2 mixed gas are 10%, 45%, and 45%, respectively. High-purity boron palladium is used as the boron source, and the sputtering pressure is 3×10 -2 Torr, the sputtering power is 10W, and the sputtering time is 45min.
[0084] In this embodiment, the flexible film cover plate 3 is a highly transparent polyimide film; the thickness of the highly transparent polyimide film is 100 μm; and the full spectrum transmittance of the highly transparent polyimide film is 91%.
[0085] The preparation method of a highly transparent polyimide film is as follows: a polyamic acid solution prepared by uniformly mixing diisopropyl phthalate, 4,4'-difluorophthalic anhydride and dimethyl sulfoxide in a molar ratio of 1:1:4 is coated on a glass substrate by an extrusion coating method; then, the coated substrate is placed in an oven and subjected to a heat treatment at 400°C to promote the polymerization reaction of the polyamic acid solution to form a polyimide film; after the heat treatment is completed, the temperature is cooled to room temperature at a cooling rate of 2°C / min, and the polyimide is demolded from the substrate to obtain a highly transparent polyimide film after treatment.
[0086] In this embodiment, the multifunctional film layer 1 is an anti-glare film, and the thickness of the multifunctional film layer 1 is 20 μm; the polarizer 5 is a polycarbonate film, and the thickness is 50 μm; the film encapsulation layer 8 is a polyethylene film, and the thickness is 65 μm; the flexible supporting layer 10 is a polyimide film, and the thickness is 35 μm; the buffer layer 11 is a polyurethane foam layer, and the thickness is 150 μm, and the porosity is 50%; the flexible metal layer 12 is a stainless steel layer, and the thickness is 100 μm.
[0087] The preparation method of the above-mentioned boron nitride-based capacitive flexible touch screen is the same as that of Example 1.
[0088] Comparative Example 1:
[0089] Different from the first embodiment, the transparent insulating boron nitride-based touch electrode module 7 does not include the first boron nitride layer 71 , and the upper indium tin oxide layer 72 is directly bonded to the third optically transparent adhesive OCA layer 6 .
[0090] Comparative Example 2:
[0091] Different from the first embodiment, the transparent insulating boron nitride-based touch electrode module 7 does not contain the first boron nitride layer 71 , the fourth boron nitride layer 77 , and the lower indium tin oxide layer 76 is directly bonded to the thin film encapsulation layer 8 .
[0092] Comparative Example 3:
[0093] Different from the first embodiment, the transparent insulating boron nitride-based touch electrode module 7 does not include the first boron nitride layer 71 , the second boron nitride layer 73 , the third boron nitride layer 75 and the fourth boron nitride layer 77 .
[0094] The performance parameters of the capacitive flexible touch screens based on boron nitride of Examples 1-3 and Comparative Examples 1-3 are summarized in Table 1.
[0095] Capacitive flexible touch screen transmittance test: using Yuanfang HAM-300 high-precision spectroscopic haze meter, refer to the latest standards of ASTMD1003 and GB / T 2410.
[0096] Indium tin oxide square resistance test in capacitive flexible touch screen: The square resistance test of indium tin oxide is carried out in accordance with GB / T 12631-1990.
[0097] The stability test performance parameters of the capacitive flexible touch screens based on boron nitride of Examples 1-3 and Comparative Examples 1-3 are statistically shown in Table 2.
[0098] The stability test adopts high temperature heating method: the test is carried out according to GB / T2423.1-2008, the test temperature is 60℃ for 2 hours, and then the performance parameters of the capacitive flexible touch screen based on boron nitride are tested, mainly including the transmittance of the touch screen and the square resistance of indium tin oxide.
[0099] Table 1 Performance parameters of capacitive flexible touch screen
[0100]
[0101] Table 2 Stability test performance parameters of capacitive flexible touch screen
[0102]
[0103] Compared with Example 1 in Table 1, when the transparent insulating boron nitride-based touch electrode module 7 does not contain the first boron nitride layer 71, when the upper indium tin oxide layer 72 is directly bonded to the third optically transparent adhesive OCA layer 6, the square resistance of the indium tin oxide increases from 72Ω / sq to 86Ω / sq, and this increased square resistance value is due to the lack of the first boron nitride layer 71. The first boron nitride layer 71 usually has a relatively high electrical insulation and can provide better conductivity for indium tin oxide. In the absence of the first boron nitride layer 71, the bonding contact between the upper indium tin oxide layer 72 and the OCA layer leads to increased electron scattering and an increase in square resistance. Therefore, the lack of the first boron nitride layer 71 leads to an increase in the square resistance of the upper indium tin oxide 72. As can be seen from Table 2, after the thermal stability test, it can be clearly seen that the lack of the first boron nitride layer 71 leads to a significant increase in the square resistance of the upper indium tin oxide 72, which further illustrates that boron nitride can improve the stability between the indium tin oxide layer and the OCA.
[0104] Compared with Example 1, Example 2 in Table 1 shows that the transparent insulating boron nitride-based touch electrode module 7 does not contain the fourth boron nitride layer 77. When the lower indium tin oxide layer 76 is directly bonded to the thin film encapsulation layer 8, the square resistance of the indium tin oxide increases from 72Ω / sq to 92Ω / sq. Similarly, the bonding contact between the indium tin oxide layer and the OCA layer causes the increase in electron scattering and the increase in square resistance. It can be seen from Table 2 that after the thermal stability test, it can be clearly seen that the lack of the fourth boron nitride layer 77 leads to a significant increase in the square resistance of the lower indium tin oxide 76, which also shows that boron nitride can improve the stability between the indium tin oxide layer and the OCA.
[0105] Compared with Example 1 in Example 3 in Table 1, the transparent insulating boron nitride-based touch electrode module 7 does not contain the first boron nitride layer 71, the second boron nitride layer 73, the third boron nitride layer 75 and the fourth boron nitride layer 77, so the indium tin oxide is all bonded to the OCA layer, which further increases the scattering of electrons and the increase of square resistance.
[0106] It can be seen from Table 2 that the lack of a boron nitride layer causes the stability between the high-temperature indium tin oxide layer and the OCA layer to deteriorate. Therefore, from the transmittance and square resistance values in Tables 1 and 2, it can be seen that the addition of a boron nitride layer can improve the problem of poor electrical insulation and stability between indium tin oxide and OCA.
Claims
1. A capacitive flexible touch screen based on boron nitride, characterized in that: The capacitive flexible touch screen comprises, from top to bottom, a multifunctional film layer (1), a flexible film cover plate (3), a polarizer (5), a transparent insulating boron nitride-based touch electrode module (7), a film encapsulation layer (8), a flexible support layer (10), a buffer layer (11) and a flexible metal layer (12); The transparent insulating boron nitride-based touch electrode module (7) comprises, from top to bottom, a first boron nitride layer (71), an upper indium tin oxide film (72), a second boron nitride layer (73), a fifth optically transparent adhesive (OCA) layer (74), a third boron nitride layer (75), a lower indium tin oxide film (76) and a fourth boron nitride layer (77); the first boron nitride layer (71), the second boron nitride layer (73), the third boron nitride layer (75) and the fourth boron nitride layer (77) are all hexagonal boron nitride layers.
2. The capacitive flexible touch screen based on boron nitride according to claim 1, characterized in that: The hexagonal boron nitride layer is a large crystal domain hexagonal boron nitride layer, and the average crystal domain of the hexagonal boron nitride is 2 to 6 mm; The thickness of the first boron nitride layer (71), the second boron nitride layer (73), the third boron nitride layer (75) and the fourth boron nitride layer (77) is 5 to 25 nm.
3. The capacitive flexible touch screen based on boron nitride according to claim 1, characterized in that: The method for preparing the transparent insulating boron nitride-based touch electrode module (7) comprises the following steps: S1: magnetron sputtering an indium tin oxide film on a copper foil, then patterning the indium tin oxide film, and then etching the copper foil with FeCl3 having a mass concentration of 5 to 15%, and using the prepared indium tin oxide film as an upper indium tin oxide film (72) and a lower indium tin oxide film (76); S2: Using a magnetron sputtering method, an upper indium tin oxide film (72) and a lower indium tin oxide film (76) are suspended in a magnetron sputtering chamber, a first boron nitride layer (71) and a second boron nitride layer (73) are sputtered on the upper and lower surfaces of the upper indium tin oxide film (72), and a third boron nitride layer (75) and a fourth boron nitride layer (77) are sputtered on the upper and lower surfaces of the lower indium tin oxide film (76), and then the second boron nitride layer (73) and the third boron nitride layer (75) are bonded together by a fifth optically transparent adhesive (OCA) layer (74), and finally a transparent insulating boron nitride-based touch electrode module (7) is obtained.
4. The capacitive flexible touch screen based on boron nitride according to claim 3, characterized in that: The magnetron sputtering method comprises: at a base pressure of 2×10 -10 In Torr's ultra-high vacuum magnetron sputtering chamber, a high-purity H2 / Ar / N2 mixed gas is used as the reaction gas. The volume percentages of H2, Ar, and N2 in the H2 / Ar / N2 mixed gas are 6-10%, 45-47%, and 45-47%, respectively. High-purity boron palladium is used as the boron source, and the sputtering pressure is (1-3)×10 -2 Torr, the sputtering power is 6 to 10 W, and the sputtering time is 15 to 45 min.
5. The capacitive flexible touch screen based on boron nitride according to claim 1, characterized in that: The thickness of the upper indium tin oxide film (72) and the lower indium tin oxide film (76) is 50 to 125 μm, and the thickness of the fifth optically transparent adhesive OCA layer (74) is 30 to 70 μm.
6. The capacitive flexible touch screen based on boron nitride according to claim 1, characterized in that: The flexible film cover plate (3) is a highly transparent polyimide film; the thickness of the highly transparent polyimide film is 50-150 μm; the full spectrum transmittance of the highly transparent polyimide film is greater than 90%.
7. The capacitive flexible touch screen based on boron nitride according to claim 6, characterized in that: The method for preparing the highly transparent polyimide film is as follows: a polyamic acid solution prepared by uniformly mixing diisopropyl phthalate, 4,4'-difluorophthalic anhydride and dimethyl sulfoxide in a molar ratio of 1:1:4 is coated on a glass substrate by an extrusion coating method; then, the coated substrate is placed in an oven and subjected to a heat treatment at 250 to 400° C. After the heat treatment is completed, the temperature is cooled to room temperature at a cooling rate of 0.2 to 2° C. / min; the polyimide is then stripped from the substrate to obtain a highly transparent polyimide film.
8. The capacitive flexible touch screen based on boron nitride according to claim 1, characterized in that: The multifunctional film layer (1) is an anti-glare film or an anti-scattering film, and the thickness of the multifunctional film layer (1) is 10 to 25 μm; The polarizer (5) is a polycarbonate film with a thickness of 40 to 80 μm; The film encapsulation layer (8) is a polyethylene film or a polyester film with a thickness of 40 to 90 μm; The flexible support layer (10) is a polyimide film or a polyethylene terephthalate film, and has a thickness of 20 to 50 μm; The buffer layer (11) is a polyurethane foam layer or a polyacrylate foam layer, with a thickness of 100 to 200 μm and a porosity of 20 to 50%; The flexible metal layer (12) is a stainless steel layer or an aluminum foil layer, and has a thickness of 50 to 120 μm.
9. The capacitive flexible touch screen based on boron nitride according to any one of claims 1 to 8, characterized in that: The multifunctional film layer (1) and the flexible film cover plate (3) are bonded together via a first optically transparent adhesive OCA layer (2); the flexible film cover plate (3) and the polarizer (5) are bonded together via a second optically transparent adhesive OCA layer (4); the polarizer (5) and the touch electrode assembly module (7) are bonded together via a third optically transparent adhesive OCA layer (6); and the film encapsulation layer (8) and the flexible support layer (10) are bonded together via a fourth optically transparent adhesive OCA layer (9); The thickness of the first optically transparent adhesive OCA layer (2), the second optically transparent adhesive OCA layer (4), the third optically transparent adhesive OCA layer (6) and the fourth optically transparent adhesive OCA layer (9) are all 20 to 100 μm.
10. A method for preparing a capacitive flexible touch screen based on boron nitride as claimed in claim 9, characterized in that: The following steps are involved: First, a large-area flexible metal layer (12) is prepared, and then a buffer layer (11) and a flexible support layer (10) are prepared thereon in sequence. Then, a thin film encapsulation layer (8) is used to encapsulate the lower surface of a transparent insulating boron nitride-based touch electrode module (7), and the thin film encapsulation layer (8) is bonded to the flexible support layer (10) through a fourth optically transparent adhesive OCA layer (9); then, a polarizer (5) is bonded to the upper surface of the transparent insulating boron nitride-based touch electrode module (7) in sequence through a third optically transparent adhesive OCA layer (6); then, a flexible film cover plate (3) is bonded to the upper surface of the polarizer (5) through a second optically transparent adhesive OCA layer (4); and finally, a multifunctional film layer (1) is bonded to the upper surface of the flexible film cover plate (3) through a first optically transparent adhesive OCA layer (2), thereby completing the preparation of a capacitive flexible touch screen.
Citation Information
Patent Citations
A large and medium-sized capacitive touch screen with a bridge structure
CN109375836A
Flexible capacitive temperature sensor and manufacturing method thereof
CN111537098A